The Preference-Driven Lead User Method for New Product Development A Comprehensive Way to Stimulate Innovations with Internal and External Sources - Sänn, Alexander (Forschungs-/Entwicklungs-/Innovations-Management, 2017)
XXII, 235 p. 20 illus.